(untitled) (Proceedings of Faculty of Civil Engineering, 2024)
The paper presents a calculation method that can be used to model the dynamics of emptying and filling retention basins intended for the temporary retention of water, i.e. to achieve the necessary transformation of the flood wave hydrograph. The calculation method is based only on the principle of mass conservation and is therefore very simple and attractive for practical application (assuming that dynamic phenomena can be reasonably neglected). To verify the effectiveness of retention for the relevant hydrological extreme conditions, the temporal change in water level must be determined by solving the mass conservation equation, which correlates the resulting change in water volume in the retention and the difference in mass flows at the inlet and outlet of the retention in the same time period. The presented procedure takes into account the inflow of water from the surface flow and the inflow of water resulting from precipitation above the retention basin. Therefore, for water flows at the outlet, the following are taken into account: the water flow under pressure through the outlet, the water flow over the spillway crest and the infiltration flow at the bottom of the retention basin. The calculation method was reduced to a simple numerical solution of an ordinary and non-linear differential equation of the first order.